Projection of Climate Variation in Qilian Mountains Based on CMIP6 - Linjun HAN; Aijuan BAI; Xuemin PU (Gaoyuan qixiang, 2022)
In this paper， the ability of CMIP6's 10 global climate models to simulate the historical climate change of Qilian Mountains is tested by using a variety of test parameters.We found that the CESM2-WACCM model has the best simulation effect on projection of climate variation in Qilian Mountains.Therefore， the variation characteristics of temperature， precipitation and humidity in Qilian Mountains from 2020 to 2064 are analyzed under three emission scenarios.They are low， medium and high emission scenario.The results are as follows： （1） In the next half century， the temperature at northern part of Qilian Mountains will be higher， lower at the southern part and higher at both ends， the possibility of heating up is high， the characteristics of warm winter are more obvious than that of warm summer.Comparing the future rise amplitude of Qilian Mountains temperature under different scenarios， it is found that under the high emission scenario， the temperature rises most significantly in winter and summer， while the rise amplitude of medium emission scenario is the lowest.（2） In the future， the precipitation in Qilian Mountains will increase in summer， and the possibility of "humidification" is relatively large.Especially under the scenario of high emission， the intensity of "humidification" is the highest in the eastern part of Qilian Mountains， and it is consistent with the water vapor convergence area shown by the divergence of water vapor flux.（3） The future water vapor variation in Qilian Mountains expressed by atmospheric specific humidity show that atmospheric humidity is more likely to increase in summer， and the variation in southern Qilian Mountains is obvious than that in Northern Qilian Mountains， especially in the scenario of high emission， the East will become more humid in the future， which is consistent with the increase of future precipitation in Qilian Mountains.